2021
DOI: 10.1108/sasbe-03-2021-0055
|View full text |Cite
|
Sign up to set email alerts
|

Organizing worn-out neighborhoods with the new-urbanism approach using mixed methods in Rudsar, northern Iran

Abstract: PurposeThe vulnerability of worn-out textures in the face of natural disasters is one of the most significant challenges that have forced planners and urban managers to intervene in these structures. In this context, the new-urbanism, or the new urbanization, movement is one of the most novel approaches. This paper aims to organizing one of the worn-out neighborhoods in Rudsar, northern Iran with an approach toward the new urbanism.Design/methodology/approachThe procedure adopted in this research is a combinat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 68 publications
2
1
0
Order By: Relevance
“…Moreover, adequate lighting in narrow alleys that have an organic and worn texture can help prevent crime and subsequently, improve spatial legibility and economic prosperity-a finding aligned with those of previous studies [99][100][101][102]. Meanwhile, the appropriate cultural-economic use of vacant land, such as the establishment of the Tea Museum as one of the main tourism hubs of Lahijan city, has an undeniable influence on the vitality and sustainability of these neighborhoods.…”
Section: Discussionsupporting
confidence: 71%
“…Moreover, adequate lighting in narrow alleys that have an organic and worn texture can help prevent crime and subsequently, improve spatial legibility and economic prosperity-a finding aligned with those of previous studies [99][100][101][102]. Meanwhile, the appropriate cultural-economic use of vacant land, such as the establishment of the Tea Museum as one of the main tourism hubs of Lahijan city, has an undeniable influence on the vitality and sustainability of these neighborhoods.…”
Section: Discussionsupporting
confidence: 71%
“…As a result, there seems to be an association between the configurational aspects of legibility and the location of historical monuments in the study area. This finding is also aligned with previously conducted studies, which confirmed that an irregular spatial configuration may possess a lower value of legibility [ 91 , 92 , 93 ]. In addition, the results were found to be consistent with respect to prior studies, which affirmed that urban development can lead to decreasing levels of legibility and accessibility [ 44 , 94 , 95 ].…”
Section: Discussionsupporting
confidence: 92%
“…Curvy or dead-end roads are typically less interconnected than grid road designs. In transportation planning, "connectivity" refers to the movement across several modes of transport or capital systems [31].…”
Section: Literature Reviewmentioning
confidence: 99%